Laparoscopic resection for 125 gastroduodenal submucosal tumors - Kim, Dong Jin (The Korean Surgical Society, 2014)
PURPOSE: The present study aims to elucidate the treatment strategies of laparoscopic resection for gastroduodenal submucosal tumors (SMTs). METHODS: Data of 125 gastroduodenal STMs were collected retrospectively resected from August, 2004 to February, 2013. Surgical outcomes according to tumor locations, pathologic results and survival data for gastrointestinal stromal tumors (GISTs) were collected and analyzed. RESULTS: There were 55 male and 70 female patients with mean age 57.9 ± 12.7 years old. Mean tumor size of gastric SMTs was 2.7 ± 1.64 cm (range, 0.4-8.5 cm). GIST was the most common (n = 70, 56%). Regarding the tumor location, all the fundic lesions were GISTs and leiomyoma was occurred 58.8% of cardiac lesions. Ectopic pancreas and schwannomas were mostly located at body portion, 73% and 80%, respectively. SMTs located at duodenal bulb comprise 4 GISTs and 3 carcinoids. Surgical results comparing between lesions located at cardia, near-pylorus and else had no difference in operation time, hospital stay and complications. In terms of outcome of GIST, all patients underwent curative resection except one case of peritoneal sarcomatosis. There was one recurrence in a high risk group following resection. The cumulative 5-year disease free survival rate was 93.5% in all GISTs. There were two postoperative complications, one gastric outlet obstruction and one leakage following wedge resection. CONCLUSION: Laparoscopic wedge resection is a safe and feasible procedure for the small to medium sized gastroduodenal SMTs even their locations are near cardia or pylorus.